1998
DOI: 10.4141/s97-004
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of cadmium, fluoride and uranium in phosphogypsum process water by calcareous soil

Abstract: Poulsen, L. and Dudas, M. J. 1998. Attenuation of cadmium, fluoride and uranium in phosphogypsum process water by calcareous soil. Can. J. Soil Sci. 78: [351][352][353][354][355][356][357]. Concerns about contaminant migration from phosphogypsum (PG) repositories prompted the present study. A sequential batch procedure, in which acidic process water (PW) from a phosphate fertilizer plant was reacted with samples of a calcareous till, was employed to determine the attenuation of environmentally sensitive elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Some of researchers used PG as an industrial by‐product for the adsorption of silver 42, fluoride, uranium and cadmium 43, zinc 44, lead 45, and nickel(II) 46, 47. In 44, 45, the researchers used pre‐conditioned PG by lime and reported that it might be practical for stabilization of Zn(II) loaded PG.…”
Section: Introductionmentioning
confidence: 99%
“…Some of researchers used PG as an industrial by‐product for the adsorption of silver 42, fluoride, uranium and cadmium 43, zinc 44, lead 45, and nickel(II) 46, 47. In 44, 45, the researchers used pre‐conditioned PG by lime and reported that it might be practical for stabilization of Zn(II) loaded PG.…”
Section: Introductionmentioning
confidence: 99%
“…16 When phosphogypsum fertilizer plant process water passed through calcareous soils during a sequential batch procedure, soils became enriched in uranium; uranium removal was controlled by a combination of sorption and precipitation processes, while calcareous soils were previously shown to sorb uranium. 17 Uranium migration was progressively retarded as the amount of peat within a peat/soil mixture contained within a geochemical barrier for radioactive waste disposal cells was increased. 18 Oxidant addition and heating experiments suggest that uranium is fixed to peat as U(VI).…”
mentioning
confidence: 99%